Long-term parenteral exposure to mercury in patients with hypogammaglobulinaemia. Issue 6181 (7th July 1979) - Haeney, M R; Carter, G F; Yeoman, W B; Thompson, R A
Abstract : Patients with hypogammaglobulinaemia commonly receive regular long-term replacement therapy with a concentrate of pooled normal human immunoglobulin G (IgG) containing an organic mercury compound (thiomersal) as a preservative. In 26 such patients the total estimated mercury dosage received ranged from 4 to 734 mg (mean 157 mg) over treatment periods of six months to 17 years (mean 6.5 years). Nineteen patients (73%) had raised urine mercury concentrations, but no correlation was found between urine mercury and the age of the patient, the IgG dose, or the duration of treatment. Urine mercury concentrations are often used to control exposure and evaluate risks in exposed subjects. Hence most patients with hypogammaglobulinaemia are theoretically at risk from mercury exposure, although no clinical evidence of toxicity is yet apparent.